An Exploration of a Practical Leadership Model for Building Inclusive School Culture: A Case Study of Madrasah Ibtidaiyah (Islamic Elementary School) in Indramayu, Indonesia - Nuansah, Unang; Salam, Abdus; Aspandi, Ade; Karim, Abdul; Mazaya El Banna, Aini (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Background: Inclusive education has become a global priority, emphasizing equitable learning access for all children regardless of ability or background. However, many schools, including Islamic elementary schools (Madrasah Ibtidaiyah) in Indonesia, continue to face barriers stemming from limited teacher preparedness, unsupportive environments, and cultural resistance. These challenges highlight the need for leadership models that can transform inclusive policy into daily practice. Objective: This study aims to explore and develop a practical leadership model that strengthens inclusive school culture in Madrasah Ibtidaiyah in Indramayu, Indonesia. The model is positioned as a response to both global calls for inclusion and the local need to integrate inclusive values with Islamic educational principles. Method: Employing a qualitative multiple-case study combined with a design-based research (DBR) approach, data were gathered through semi-structured interviews, focus group discussions, classroom observations, and document analysis. Participants consisted of school principals, teachers, and parents, ensuring triangulation and comprehensive perspectives throughout all DBR cycles of analysis, design, implementation, evaluation, and refinement. Results:The study found that principals play a central role in demonstrating inclusive values through daily behavior, mentoring teachers, and encouraging collaboration with families and communities. Leadership practices such as participatory decision-making, adaptive policy enactment, and community engagement contributed significantly to the development of inclusive culture. Yet, practical challenges remained, including inadequate resources, limited training access, and varying levels of parental acceptance. Conclusion and Contribution: The research proposes an applicative leadership framework that merges participatory and adaptive leadership with Islamic moral grounding, providing a culturally relevant approach to inclusion. By linking the visionary dimension of transformational leadership with the contextual responsiveness of practical leadership, the framework offers a bridge between inclusive ideals and everyday educational realities in faith-based primary schools.